'A Present for My Daughter': Gender and Posterity in Victorian Inter-generational Life Writing. Issue 4 (2nd October 2022) - Burke, Lois
ABSTRACT: This article utilises a unique collection of life-writing manuscripts to reconsider generational difference, father/daughter relationships, and autobiography in nineteenth-century England. Although stemming from a family tradition of life writing, Martha Ann Howlett's late-Victorian memoirs render a critical image of her upbringing and promote a vision of social and financial independence for the next generation of women. These memoirs sit in contrast to her father Samuel Burt Howlett's 'present' to Martha Ann—his series of autobiographical volumes composed during her childhood—which borrow from multiple modes of life writing that prevailed in the early Victorian era. This collection, which has never been studied before, permits an understanding of complex and composite father/daughter relationships as told through life writing. Sustained comparative study of the two interconnected examples of life writing reveals the opposing narratives of continuation and disruption in the family's record. These manuscripts ultimately demonstrate the importance of generational thought to life writing's power to self-define, and expose the gendered (though contested) understandings of work, creativity, education, and family contained within relational archives.